Start with hello : how to convert today's stranger into tomorrow's client - Coles, Linda (Wiley, 2013)
What's the first step to success? Start with Hello! Start with Hello reveals the skill that so many successful people share; talking to strangers. That is, the ability to engage with strangers in productive and creative ways, and turn them into valuable professional contacts. Packed with tips and inspiring true stories, Start with Hello will show you how to: be in the right place at the right time for networking take the first step in starting a new conversation make a positive first impression build strong business relationships online and offline expand your circle of friends and colleagues. Whatever business you are in, your success depends on the relationships you build. That person sharing the lift with you could just become a future business partner, a career-changing connection or a lifelong friend. If you want to boost your prospects in business and in life, just Start with Hello .